2014
DOI: 10.1002/jmor.20281
|View full text |Cite
|
Sign up to set email alerts
|

Diverse pereopodal secretory systems implicated in thread production in an apseudomorph tanaidacean crustacean

Abstract: Among arthropods, various insects, spiders, and crustaceans produce thread. The crustacean Tanaidacea include species that use thread mainly to construct dwelling tubes. While thread production was previously known only in Tanaoidea and Paratanaoidea, it was recently discovered in two species in Kalliapseudidae (Apseudoidea), although information on the morphology of the thread-producing system was lacking. Using histology, light and scanning electron microscopy, we found that the kalliapseudid Phoxokalliapseu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In Mesokalliapseudes macsweenyi (Drumm, 2003) and Psammokalliapseudes granulosus Silva Brum 1973, similar mucus glands are involved in the in the construction of their fragile mucus tubes (Drumm 2005). Also, Kakui and Hiruta (2014) reported that such glands are involved in the production of the fine, thread-producing mucus strands in Phoxokalliapseudes tomiokaensis (Shiino, 1966). …”
Section: Mucus Glandsmentioning
confidence: 99%
“…In Mesokalliapseudes macsweenyi (Drumm, 2003) and Psammokalliapseudes granulosus Silva Brum 1973, similar mucus glands are involved in the in the construction of their fragile mucus tubes (Drumm 2005). Also, Kakui and Hiruta (2014) reported that such glands are involved in the production of the fine, thread-producing mucus strands in Phoxokalliapseudes tomiokaensis (Shiino, 1966). …”
Section: Mucus Glandsmentioning
confidence: 99%
“…Binuclearity is typically regarded as a prominent feature of lobed glands (Talbot and Demers, 1993) and is occasionally used as a diagnostic character (Kakui and Hiruta, 2014). However, the secretory cells in lobed glands contain one or two nucleuses, apparently independent of cell size (Gorvett, 1951).…”
Section: Secretory Cell Nucleus Quantitymentioning
confidence: 99%
“…9G-H) (Blanc, 1884), all of which might be defined as pseudotubular. Building glands in other crustaceans suggest another structure; the amphipods Crassicorophium bonellii and Lembos websteri and the tanaid Phoxokalliapseudes tomiokaensis (Shiino, 1966) have lobed and typical rosette glands (Kronenberger et al, 2012b, Kakui andHiruta, 2014), while callianassid shrimps (Decapoda) have only typical rosette glands (Dworschak, 1998). Cirripedian cement glands are multicellular but do not possess special duct cells (Lacombe and Liguori, 1969) and might be considered tubular gland variations (class 1 glands, according to the Noirot and Quennedey classification, 1974).…”
Section: Comparison With Other Arthropod Silk Glandsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thread-producing species have evolved independently in many different crustacean groups, and they exhibit a variety of spinneret systems [ 13 ]. The Tanaidacea, where adults typically bear a pair of remarkable claws and show a well-developed tube-dwelling behavior, is one of the most thread-dependent taxa in the Crustacea.…”
Section: Introductionmentioning
confidence: 99%